2022
DOI: 10.1017/jmo.2022.79
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking work: How approach and avoidance features of cognitive crafting are linked with job crafting behaviors and work engagement

Abstract: Responding to the call for more research on cognitive crafting, this study focuses on employees' reframing of their job characteristics to assign higher importance to job resources and downplay the relevance of costly job demands. Furthermore, it examines how these proactive cognitive strategies are embedded in an overall job crafting process, including both cognitive and behavioral aspects, and linked with work engagement. Preliminary results (n = 247) support the conceptualization of cognitive crafting encom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
(122 reference statements)
0
1
0
Order By: Relevance
“…Given that flow metacognition entails the “perceptions of the usefulness of flow at work for job performance”, from a theoretical perspective, it makes sense that these beliefs may increase flow and drive the outcomes of performance and engagement, but not burnout. Burnout has more to do with a depletion of personal resources, rather than the allocation of cognitive control toward the utilization of these resources (Costantini, 2022 ). Therefore, while flow itself can reduce burnout, the belief that flow is useful or not for performance may be theoretically unrelated to whether employees experience burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Given that flow metacognition entails the “perceptions of the usefulness of flow at work for job performance”, from a theoretical perspective, it makes sense that these beliefs may increase flow and drive the outcomes of performance and engagement, but not burnout. Burnout has more to do with a depletion of personal resources, rather than the allocation of cognitive control toward the utilization of these resources (Costantini, 2022 ). Therefore, while flow itself can reduce burnout, the belief that flow is useful or not for performance may be theoretically unrelated to whether employees experience burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Schuler and Brunner (2009, p. 173) observed that the flow experience in marathons is related to the motivation to run in the future: "Flow functions as a reward of the running activity, which leads to the desire to perform the activity again" (p. 173). Recent research on how flow leads to addictive behavior also stated that when individuals feel in control of the situation and are experiencing positive emotions caused by flow, they may even underestimate the risks and continue to pursue similar and higher-level challenges (Costantini, 2022;Ramsey & Lorenz, 2020;Zimanyi & Schüler, 2021). Thus, we propose the following hypothesis: Hypothesis 2a: Workflow experience is positively associated with challenging demands.…”
Section: An Upward Spiral Triggered By Flow Experiencementioning
confidence: 90%